(untitled) - Micklos, David A. (Cold Spring Harbor, NY, 2003)
This is the second edition of a highly successful textbook (over 50,000 copies sold) in which a highly illustrated, narrative text is combined with easyÂ–toÂ–use thoroughly reliable laboratory protocols. It contains a fully up to date collection of 12 rigorously tested and reliable lab experiments in molecular biology, developed at the internationally renowned Dolan DNA L
Keywords: Molecular biology.,Molecular biology; Laboratory manuals